The Role of Critical Thinking and Rhetorics in Upbringing - Baranova, Jūratė (Acta Paedagogica Vilnensia, 2012)
This article deals with the problem of a paradoxical opposition between critical thinking and the art of rhetorics in upbringing. Is it neccessary for the formation of critical thinking to stress also its exterior form? For example, is it necessary to pay tribute to its rherotical expression? Or maybe rhetorics is only secondary, not necessary in critical thinking? Is it possible for rhetorics to substitute critical thinking or to suspend its power? These questions are raised in the article for the reason that rhetorics in Lithuania is not included into programmes of developing critical thinking or is suggested as an additional issue only in the teaching of literature. The author of the article re-flects upon the sceptical attitude towards rhetoric in ancient Greece, discussed in Plato’s works, mentions also doubts about the value of rhetorics in Descartes’ and Locke’s works, describes also the Kantian attitude. On the other hand, the article reveals the positive aspects of rhetoric, noted by philosophers of Ancient Rome by and Italian humanists. A special note is given to Italian philosopher Grassi’s conceptions. The author agrees with Grassi that reasoning is not able to avoid the rhetorical form, that even the concepts of “axiom” or “reasons” are metaphors.The author concludes that metaphors do not negate or oppose critical thinking, but extend its power of knowledge. On the other hand, a metaphor is not able to substitute critical thinking. So, these two epistemic powers should be formed and educated as parallel and autonomous capacities. In the case when the metaphorical vision and critical thinking are educated as separate capacities, the result is not sutisfactory. A metaphorical rhetorical accent in education without critical thinking forms a too chaotic, lyrical, undisciplined thinking, stressing the subjective self-expression based on the presupposition that rhetroical expression is more important than truth. On the other hand, stressing only critical thinking in education results in a too formal reasoning neglecting reality and the meaning of contingency. The author’s theoretical conclusion that these two epistemic powers of personality could be educated in harmony is also practically implemented in her philosophy texbooks for schools, uniting philosophical thought, literature, and visual art.
Keywords: critical thinking; rhetorics in upbringing; education; philosophy of education